2016
DOI: 10.4103/0974-7796.164842
|View full text |Cite
|
Sign up to set email alerts
|

Is scoring system of computed tomography based metric parameters can accurately predicts shock wave lithotripsy stone-free rates and aid in the development of treatment strategies?

Abstract: Objective:The objective was to determine the predicting success of shock wave lithotripsy (SWL) using a combination of computed tomography based metric parameters to improve the treatment plan.Patients and Methods:Consecutive 180 patients with symptomatic upper urinary tract calculi 20 mm or less were enrolled in our study underwent extracorporeal SWL were divided into two main groups, according to the stone size, Group A (92 patients with stone ≤10 mm) and Group B (88 patients with stone >10 mm). Both groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…Accumulation of surgical experience was a significant predictor for stone‐free status; the number of stones showed a statistically significant difference between the successful and the remnant stone groups. According to the study of Badran et al ., the SFR was significantly higher in patients with HU <830 . Ganpule et al .…”
Section: Discussionmentioning
confidence: 93%
“…Accumulation of surgical experience was a significant predictor for stone‐free status; the number of stones showed a statistically significant difference between the successful and the remnant stone groups. According to the study of Badran et al ., the SFR was significantly higher in patients with HU <830 . Ganpule et al .…”
Section: Discussionmentioning
confidence: 93%
“…The stone sizes included was heterogenous, with minimum sizes used in 23 studies, documented as 4 mm, 5 mm, 6 mm, and 10 mm in 2, 19, 1, and 1 study, respectively [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Maximum stone sizes were used in all 28 studies listed as 10 mm, 15 mm, 20 mm, 25 mm, and 30 mm, assessed in 1, 3, 21, 2, and 1 studies, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies measured the stones on a single axial plane that displayed the stone at its maximal diameter [ 13 , 18 , 19 , 27 , 30 , 34 •, 35 ]. Whilst others took the average HU from ROIs in three separate axial planes: the upper pole, the stone at its maximal diameter, and the lower pole [ 11 , 12 ]. A single study defined MSD as the average of the minimum and maximum HU readings [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…They described SSD as the only significant factor for prediction of ESWL success and they attributed that to loss of shock waves energy during penetration through excess body fat with increased SSD. 9 Also, Badran et al 17 suggested that shock waves lose their energy by 10% to 20% for every 6-cm penetration and Perks et al 18 defined 90 mm as the threshold value for SSD beyond which the success rate decreases. While, Waqas et al 1 reported that SSD of 100 mm as a cut off value with success rate of 71% in patients having SSD less than 100 mm.…”
Section: Discussionmentioning
confidence: 99%